The State Sanitary Inspection as the organization accomplishing tasks within the scope of public health - Nawrocka, Elżbieta (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The Sanitary Inspection was established in the early post-war years and makes part of the health protection system in Poland which accomplishes the tasks within the scope of public health. The organs of the State Sanitary Inspection function based on the act from 14th March 1985 about the State Sanitary Inspection (Dz. U. z 2006r. Nr 122 poz. 851 with later changes) and realizes Polish and the European Union law in the field of public health. The organizational units of the State Sanitary Inspection realize the tasks taking preventive and current sanitary control and leading preventive and anti-epidemiological activity according to infectious diseases and also promoting healthy lifestyle. The sanitary-epidemiological ‘situation of Poland is shown in the annual report prepared by The General Sanitary Inspectorate.